Effect of liming and phosphorus application on performance of Leucaena leucocephala in acid soils - Duguma, B.; Kang, B.T.; Okali, D.U.U. (1988)
Pot experiments were conducted to assess the lime and phosphorus requirements ofLeucaena leucocephala (LAM.) De Wit grown on three acid soils (Ultisols) from southeastern Nigeria. Liming and phosphorus application significantly enhanced growth ofL. leucocephala. Ammakama soil showed best effect to phosphorus application, while acidity problems were more pronounced on Onne and Isienu soils. High lime rate (2000 ppm) reduced plant growth in Isienu soil probably due to nutrient imbalance. Potassium, manganese and zinc levels in the plants were reduced with increasing lime rates. On Onne and Isienu soils plant tops correlated better with total acidity and extractable Al+3 level than with soil pH-H2O.